Case report: Crigler-Najjar syndrome type 1 in Croatia—more than a one in a million: a case series - Kovačić Perica, Matea; Todorić, Ivana; Marčinković, Nedo; Džepina, Petra; Aničić, Mirna Natalija; Mrzljak, Anna; Vuković, Jurica (Frontiers in Pediatrics, 2023)
Crigler-Najjar syndrome (CNS) is an exceedingly rare autosomal recessive disease with an estimated incidence of 1 in a million live births. CNS type 1 (CNS1) is the most severe form, characterized by severe unconjugated hyperbilirubinemia since birth due to the absence of hepatic uridine 5'-diphosphate glucuronyltransferase (UGT1A1) activity. Daily phototherapy (PT) and liver transplant (LT) are the mainstays of therapy. Here, we present a higher-than-expected incidence of CNS1 in Croatia (6,1 in a million). In the last 31 years, we treated eight CNS1 patients from five families with no reported consanguinity. Four patients are descendants of an isolated enclave in Kosovo with a small gene pool and a high potential for inbreeding. Severe unconjugated hyperbilirubinemia was verified in a neonatal period and PT was initiated. Four patients underwent LT from living-related donors. One of them had unsuccessful hepatocyte transplantation earlier. LT was successful in three patients, and one patient died due to primary graft dysfunction. Four patients are currently treated with 9–12 h daily PT with inconsistent disease control, and gradually increasing bilirubin. One patient developed kernicterus before LT, while others have normal psychomotor development and no neurologic impairment. Genetic testing of the UGT1A1 gene in six patients from three families revealed three different homozygous mutations (c.722_723 delAG, c.717_718 delAG, and c.1021 C >T), all previously described in other populations. There is a possibility of the founder effect as an explanation for the higher incidence of CNS1 in at least a subgroup of Croatians.